Madhya Pradesh Rajya Van Vikas Nigam Limited - a Cameo - Singh, D. P. (Indian Forester, 1991)
The paper describes the genesis and activities of Madhya Pradesb Rajya Van Vikas Nigam. Starting from 1976 with an authorised capital of Rs. 20 crores it has built up assets in the form of plantations of Teak, Bamboo and other species spread over an area of 1.27 lakh ha till 1991. The worth of these plantations today is approximately Rs. 100 crores. The Nigam is fully aware of its social and environmental obligations and all its projects, present and future, are formulated to help fully discharge these obligations along with maintaining commercial viability.